A history of Thailand - Baker, Christopher John 1948- (Cambridge University Press, 2009)
In A History of Thailand, Chris Baker and Pasuk Phongpaichit reveal how a world of mandarin nobles and unfree labour evolved into a rural society of smallholder peasants and an urban society populated mainly by migrants from southern China. They trace how a Buddhist cosmography adapted to new ideas of time and space, and a traditional polity was transformed into a new nation-state under a strengthened monarchy. The authors cover the contests between urban nationalists, ambitious generals, communist rebels, business politicians, and social movements to control the nation-state and redefine its purpose. They describe the dramatic changes wrought by a booming economy, globalization, and the evolution of mass society. Finally, they show how Thailand's path is still being contested by those who believe in change from above and those who fight for democracy and liberal values. Drawing on new Thai-language research, this second edition brings the Thai story up to date and includes a new section on the 2006 coup and the restoration of an elected government in 2008